Economic Condition of the People of Bromo Tengger Semeru as International Tourism in Indonesia During the Pandemic - Anastasya Kristi; Annisa Ilman Nafia; Handriyono Handriyono (UPT Penerbitan Universitas Jember, 2021)
The tourism and agriculture sectors are important aspects of economic life for the people of Bromo. However, since the pandemic that almost destroyed the economic sector in almost all corners of the world, it also affected the BromoTengger Semeru area. This study aims to determine the effect of the pandemic on the economic sector of the BromoTengger Semeru community before and after the pandemic. This study will use a qualitative method by distributing questionnaires and direct observations in order to find out the economic condition of the Bromo community before and after the pandemic and analyze how the Bromo community deals with these conditions. The results of this research and observation are that the majority of the tengger people in the Sukapura sub-district affected by the pandemic experienced a decrease in income. However, the economy in general can still face this pandemic because people have income in the agricultural sector. So that the decline in social welfare does not change drastically. Keywords: Economy, Income, Human Resource, Pandemic, Tourism.